Licensed Surveyor Role Analysis for Achieving Indonesia Complete Systematic Land Registration (PTSL) in 2024. Issue 1 (1st January 2023) - Suranto; Djojomartono, Prijono Nugroho
Abstract: In 2020 Directorate General of Land and Spatial Survey and Mapping composed a 2020 until 2024 national priority roadmap for the Complete Systematic Land Registration (PTSL) priority program towards a positive publication system that will be implemented in Indonesia in 2023. The estimated number of land parcels in Indonesia are 126.000.034, while until January 2022 the number of certified land parcels are 79.260.203. Therefore, the licensed surveyor role is massively needed to support the completion of PTSL. Licensed surveyors consist of Cadastral Surveyor (SK) and Assistant Cadastral Surveyor (ASK). According to Ministry of Agrarian Affairs (ATR/BPN) data until December 2021, there are 1, 432 SKs and 6, 947 ASKs throughout Indonesia. However, they are unevenly distributed all over Indonesian provinces. This research uses quantitative data analysis that analyses 126 million land parcels roadmap analysis data, registered land parcels until January 2022, and licensed surveyor data until December 2021. The proportional workload analysis approach of licensed surveyors is used for analyzing the participation of licensed surveyors, in order to realize PTSL in 2024 in Indonesia. The workload analysis is a modification of the State Apparatus Minister Decree (SK MenPAN) No. KEP/75/M.PAN/7/2004 concerning Employee Necessity Calculation Guidelines Based on Workload. Workload and its volume calculation is modified adjusting licensed surveyor workload proportionally. Licensed surveyors' workload is gained from Directorate General of Surveys and Mapping national priority roadmap data of PTSL program until 2024, with total 126 million land parcels. The results show that the composition and the number of SKs and ASKs in Indonesia are uneven and not ideal. The highest number of SKs and ASKs are in Java Island and while the smallest number of them are in Papua Island. Based on the results of the proportional workload analysis of licensed surveyors in Indonesia, under the supervision of the SK, an ASK proportional workload is 13 fields/day. Therefore, achieving complete systematic land registration in Indonesia needs strategy for equalizing ASK distribution from Java to the six provinces ASK lacking, namely: Papua (+160 people), West Papua (+101 people), Maluku (+102 people), North Sulawesi (+57 people), Aceh (+38 people), and Riau Islands (+13 people).